2015
DOI: 10.5539/gjhs.v8n4p95
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Pre-Diabetes With Body Mass Index and Marital Status in an Iranian Urban Population

Abstract: Pre-diabetes increased the development of diabetes mellitus (type 2). The aim of study was to determine the association of body weight, education and marital status with pre-diabetes in an Iranian urban population. A sample of 788 subjects (360 men and 428 women) between the ages 30–85 years participated in our study and anthropometric measurements, educational level and fasting blood sugar of participants were recorded. The t and Chi square tests were used for continuous and categorical variables. The associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 23 publications
(23 reference statements)
12
26
0
3
Order By: Relevance
“…diabetes) (Perkins et al, 2016). Similar to our findings, two studies (Azimi-Nezhad et al, 2008;Rahmanian et al, 2016) found no association between marital status and abnormal glucose tolerance. Interestingly, both studies that found no associations were conducted in Iran.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…diabetes) (Perkins et al, 2016). Similar to our findings, two studies (Azimi-Nezhad et al, 2008;Rahmanian et al, 2016) found no association between marital status and abnormal glucose tolerance. Interestingly, both studies that found no associations were conducted in Iran.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, both studies that found no associations were conducted in Iran. Azimi-Nezhad et al found no statistical difference on the prevalence of DM among married, single, divorced or widowed individuals from greater Khorasan province in northeast Iran (Azimi-Nezhad et al, 2008), while Rahmanian et al reported no statistically significant association was found between the odds of pre-diabetes and marital status among study subjects from Jahrom, Fars province in southern Iran (Rahmanian et al, 2016). Our study's methodology matched quite closely with these studies, possibly explaining our similar results.…”
Section: Discussionmentioning
confidence: 98%
“…As diabetes mellitus is related to some sociodemographic factors within the Iranian population (24), the researhcers could not find any data regarding educational, economical situations, urban-rural differences and cigarette or alcohol consumption prevalence of type 2 diabetes in Zarand, Kerman. The results conducted on educational level of males were in line with previous investigations (25,26). Rahmanian et al reported that diabetes is most prevalent in Iranian individuals with lower educational level (26).…”
Section: Discussionsupporting
confidence: 89%
“…The results conducted on educational level of males were in line with previous investigations (25,26). Rahmanian et al reported that diabetes is most prevalent in Iranian individuals with lower educational level (26). In addition, a higher prevalence of diabetes mellitus in an urban area of different Iranian provinces has usually been reported compared with rural areas (27,28).…”
Section: Discussionsupporting
confidence: 87%
“…This result was contradicted by the studies conducted in Iran. 21,23,24 BMI was highly associated with the risk of T2DM. The relation between BMI and risk of diabetes was demonstrated by Vaidya et al, 25 Pandya et al 26 and Gupta et al 17 Both insulin resistance and defective insulin secretion are most often seen among obese people, leading toward the occurrence of diabetes.…”
Section: Discussionmentioning
confidence: 90%